Serum vitamin D, calcium, and phosphorus concentrations in ponies, horses and foals from the United States and Thailand - Megan E. Pozza (2018)
Vitamin D is essential in calcium and phosphorus regulation, bone physiology, cell proliferation and epithelial integrity. Literature on vitamin D in growing horses is sparse, and the effect of age on vitamin D has not been evaluated in equids in the United States or in tropical countries. The goal of this study was to determine if there was an effect of age on serum 25(OH)D 3 concentrations in equids in the US (Ohio/Kentucky) and Thailand (Chiang Rai and Kanchanaburi) during the same time of the year. Blood samples were collected from healthy ponies (n=21) and Thoroughbred foals (n=13), yearlings (n=10), and horses (n=20) in Thailand and from Thoroughbred foals (n=10) and horses (n=17) in the US. Serum concentrations of 25(OH)D 3 , calcium and phosphorus were measured.In both countries, serum 25(OH)D 3 concentrations were lower in foals than in yearlings and adult horses. Serum 25(OH)D 3 concentrations were higher in horses than in ponies in Thailand, but were not different between horses from either country. Calcium concentrations were not different between groups or location. In both countries, phosphorus concentrations were higher in foals than in older groups; however, were not different between ponies and horses. This study shows that independent of geography there are age-related differences in 25(OH)D 3 concentrations in horses and further confirms that 25(OH)D 3 concentrations are lower in horses compared to other species. The information will serve as the basis for future clinical studies and to help understand better the pathophysiology of equine disorders associated with calcium and phosphorus dysregulation. © 2014 Elsevier Ltd.